Nuclear actin polymerization from faster growing ends in the initial activation of hox gene transcription Are nuclear speckles involved? - Naum Ongania, Gabriela (2014)
The HoxB cluster expression is activated by retinoic acid and transcribed in a collinear manner. The DNA-binding Pknox1-Pbx1 complex modulates Hox protein activity. Here, NT2-D1 teratocarcinoma cells -a model of Hox gene expression- were used to show that upon retinoic acid induction, Pknox1 co-localizes with polymeric nuclear actin. We have found that globular actin aggregates, polymeric actin, the elongating RNA polymerase II and THOC match euchromatic regions corresponding to nuclear speckles. Moreover, RNA polymerase II, N-WASP, and transcription/splicing factors p54nrb and PSF were validated as Pknox1 interactors by tandem affinity purification. PSF pulled down with THOC and nuclear actin, both of which co-localize in nuclear speckles. Although latrunculin A slightly decreases the general level of HoxB gene expression, inhibition of nuclear actin polymerization by cytochalasin D blocks the expression of HoxB transcripts in a collinear manner. Thus, our results support the hypothesis that nuclear actin polymerization is involved in the activation of HoxB gene expression by means of nuclear speckles.